Differential response of cowpea lines to aluminum and phosphorus application - Kolawole, G.O.; Tian, G.; Singh, B. (Informa UK Limited, 2000)
Two pot experiments were conducted, one to evaluate the levels of tolerance of fifteen cowpea [Vigna unguiculata (L.) Walp] lines to aluminum (Al) application, and the second to determine the effect of phosphorus (P) addition on the performance of Al‐tolerant lines (IT 91K‐93–10, IT 93K‐2046–1, and IT 90K‐2 77–2) and Al‐sensitive lines (IT 86D‐719, IT 90K‐284–2, and IT 89KD‐349) in an Alfisol with Al amendment. Fourteen of the fifteen lines tested showed decreased root biomass (between 19 to 81% reduction) with Al addition, but this effect was significant for eight of them. Fewer lines showed decreased shoot biomass and grain yield with Al application. Despite little change in nodule number following Al application, there was a significant decrease in nodule weight (between 24 and 53% reduction) for nearly all lines. Phosphorus fertilization increased shoot and root biomass, grain yield, nodule number, and weight, and nitrogen (N) and P content of nearly all lines. Al‐tolerant lines showed higher response in shoot and root biomass and nodulation to P fertilization than Al‐sensitive lines, with the highest response from IT 90K‐277–2. Increase in shoot dry weight as a result of P fertilization was from 64 to 107% for Al‐tolerant lines and from 44 to 48% for the Al‐sensitive lines, and increase in root dry weight was from 46 to 86% for the Al‐tolerant lines and from 7 to 42% for the Al‐sensitive lines. Results of these trials indicated that lines IT 91K‐93–10, IT 93K‐2046–1, and IT 90K‐277–2 have potential for good performance in soil with Al toxicity problems, and that cowpea lines with inherent genetic tolerance to Al will give higher response to P fertilization when grown in soil with Al toxicity problems.